2017
DOI: 10.1186/s12938-017-0342-y
|View full text |Cite
|
Sign up to set email alerts
|

Dependency criterion based brain pathological age estimation of Alzheimer’s disease patients with MR scans

Abstract: ObjectivesTraditional brain age estimation methods are based on the idea that uses the real age as the training label. However, these methods ignore that there is a deviation between the real age and the brain age due to the accelerated brain aging.MethodsThis paper considers this deviation and obtains it by maximizing the correlation between the estimated brain age and the class label rather than by minimizing the difference between the estimated brain age and the real age. Firstly, set the search range of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This appears to contradict what has been observed for AD, where some age-related changes such as, neural tissue thinning, neural activity and functional connectivity impairments were shown to be more pronounced in AD (Fox and Schott, 2004 ; Sperling, 2007 ; Toepper, 2017 ; Chiquita et al, 2019 ). It also appears to contradict findings in Li et al ( 2017 ) and Löwe et al ( 2016 ), where AD patients presented a positive brain-age gap (greater brain aging), and findings in Gaser et al ( 2013 ), where brain-predicted age was a significant predictor of dementia progression within 3 years of baseline MRI scan.…”
Section: Discussionmentioning
confidence: 57%
“…This appears to contradict what has been observed for AD, where some age-related changes such as, neural tissue thinning, neural activity and functional connectivity impairments were shown to be more pronounced in AD (Fox and Schott, 2004 ; Sperling, 2007 ; Toepper, 2017 ; Chiquita et al, 2019 ). It also appears to contradict findings in Li et al ( 2017 ) and Löwe et al ( 2016 ), where AD patients presented a positive brain-age gap (greater brain aging), and findings in Gaser et al ( 2013 ), where brain-predicted age was a significant predictor of dementia progression within 3 years of baseline MRI scan.…”
Section: Discussionmentioning
confidence: 57%
“…Previous research has demonstrated that the brain age gap is not only valuable to obtain a general estimate of brain health in healthy subjects but also to identify subjects at risk for mental or neurological diseases. Specifically, previous research has shown that subjects with schizophrenia, 3 Down syndrome, 4 depression, 3 and Alzheimer's disease 2,[5][6][7] show increased brain age gaps, suggestive of accelerated aging. Furthermore, recent research suggests that cardiovascular risk factors are also associated with elevated positive brain age gaps, 8 reinforcing the concept of a reciprocal heart-brain axis 9 wherein cardiac conditions impact the brain and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Various age ranges of subjects have been used for studying age prediction. For example, the subjects of 3–20 years of age were chosen for assessment of biological maturity based on age prediction [12]; the study of the advanced BrainAGE in patients with type 2 diabetes mellitus was conducted based on the subjects of 20–86 years of age [13]; the subjects of 21–65 years of age were chosen for studying the brain ageing in schizophrenia [9]; the age range of 65–85 years was used for the discussion of the dependence between brain age and Alzheimer’s disease [14]. Nonetheless, little research has been done on the age prediction of infants before 2 years of age.…”
Section: Introductionmentioning
confidence: 99%